2015
DOI: 10.1556/036.102.2015.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of naringenin on near-surface membrane fluidity in human erythrocytes

Abstract: Purpose: Deformability/rheologic behavior of erythrocytes are related to near-surface membrane fluidity. Specific agents can increase erythrocyte membrane fluidity in order to adjust hemodynamics in cardiovascular diseases. Grapefruit flavanone naringenin has been proposed for potential use in an alternative therapy of cardiovascular conditions. In respect to this, we assessed here effects of two nutritionally relevant concentrations of naringenin (0.1 and 1 µg/ml) on near-surface membrane fluidity in human er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…We also studied influence of tannins on physical state of erythrocyte membrane by EPR method. The use of fatty acids with different position paramagnetic groups as EPR probes allows to monitors changes in membrane structure at various depth (Sonmez et al 2013 ; Ajdzanovic et al 2010 , 2011 , 2015 ; Mendanha et al 2013 ; Gwozdzinski et al 2011 ). We have chosen 5-DS because tannins with big molecular mass are known to affect the membrane surface without causing significant changes in the depth of the bilayer (Olchowik et al 2012 ; Tarahovsky 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also studied influence of tannins on physical state of erythrocyte membrane by EPR method. The use of fatty acids with different position paramagnetic groups as EPR probes allows to monitors changes in membrane structure at various depth (Sonmez et al 2013 ; Ajdzanovic et al 2010 , 2011 , 2015 ; Mendanha et al 2013 ; Gwozdzinski et al 2011 ). We have chosen 5-DS because tannins with big molecular mass are known to affect the membrane surface without causing significant changes in the depth of the bilayer (Olchowik et al 2012 ; Tarahovsky 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of flavonoids to modify membrane fluidity is also particularly important because alterations in membrane fluidity have been reported to accompany a number of disease processes. , Remarkably, the administration of naringenin resulted in a substantial decrease of the erythrocyte membrane fluidity in patients with essential hypertension, when compared to healthy controls . Moreover, genistein and daidzein were also reported to reveal a softening effect on DOPC bilayers using a combination of X-ray scattering and MD simulations studies .…”
Section: Resultsmentioning
confidence: 99%
“…For example, when flavonoids partition in biomembranes, they may change their physical properties such as fluidity/rigidity and thickness. Understanding the way flavonoids change these parameters is of significant importance as this may be (in)­directly linked to therapeutic potentials, as seen by the observed impact of some flavonoids on fluidity . Another example of a key biological action of flavonoids directly attributed to their impact on biomembranes is their capacity to influence the lifetime of model ion channels, such as gramicidin A (gA). , …”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that NRG has increased the membrane fluidity near the hydrophilic surface in erythrocytes inhibiting them from being ruptured. 63 Also, NRG has the ability to diffuse through the RBCs membranes and bind to the Hb molecules leading to their stabilization without any interference with its oxygen. 64 Taking into account our results, the findings suggest that naringenin (NRG) has a positive effect on the radiation-induced spleen injury.…”
Section: Resultsmentioning
confidence: 99%